1979
DOI: 10.1111/j.1399-3054.1979.tb06527.x
|View full text |Cite
|
Sign up to set email alerts
|

Self inhibition of the Agaricus bisporus Spore by CO2 and/or γ‐Glulaminyl‐4‐hydroxybenzene and γ‐Gtutaminyl‐3,4‐benzoquinone: A Biochemical Analysis

Abstract: Chemical and enzymological analyses have been carried out to study the mode of action of CO2, in inhibiting germination in Agaricus bisporus and to test the suggestion (Vogel and Weaver, 1972. Exp. Cell Res. 75: 95, Vogel et at, 1974. Am. J. Pathol. 76: 165) that γ‐glutaminyl‐4‐hydroxybenzene (GHB) and/or γ‐glutaminyl‐3,4‐benzoquinone (GBQ) would inhibit the succinate dehydrogenase (SDH) in the mushroom spore and thus represent the causal agent(s) of its dormancy. Evidence is presented that the impairment of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The mushrooms were packed with frozen gel packs in insulated containers and shipped to our laboratory within 24 h by air express. y-L-Glutaminyl-4-hydroxybenzene (GHB) and y-L-glutaminyl-3,4dihydroxybenzene (GDHB), used as analytical standards, were extracted from mushroom gill tissue, following the procedure of Rast et al (1979), and identified by UV and 'H NMR spectroscopy (XH NMR spectra were obtained with a JEOL GX-400 instrument with D2O). l-DOPA and tyrosine were obtained from Sigma Chemical Co. All other chemicals were of reagent grade.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mushrooms were packed with frozen gel packs in insulated containers and shipped to our laboratory within 24 h by air express. y-L-Glutaminyl-4-hydroxybenzene (GHB) and y-L-glutaminyl-3,4dihydroxybenzene (GDHB), used as analytical standards, were extracted from mushroom gill tissue, following the procedure of Rast et al (1979), and identified by UV and 'H NMR spectroscopy (XH NMR spectra were obtained with a JEOL GX-400 instrument with D2O). l-DOPA and tyrosine were obtained from Sigma Chemical Co. All other chemicals were of reagent grade.…”
Section: Methodsmentioning
confidence: 99%
“…Isolation and Quantitation of GHB, Tyrosine, GDHB, and l-DOPA from Mushrooms. Apart from minor modifications, the isolation and quantitation of major substrates of PPO in mushroom were according to the procedures of Rast et al (1979) and Speroni and Beelman (1982), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence suggests that CO2 indirectly inhibits succinic dehydrogenase activity, inducing a meta bolic block and maintaining spore dormancy (75). The metabolic block and hence, dormancy, are relieved by the addition of isovaleric acid.…”
Section: Entrance Into Dormancymentioning
confidence: 99%
“…Oxidation of GHB by Tyrosinase in the Presence of Sinapic Acid. GHB, the most predominant phenolic substrate of tyrosinase in mushroom sporophores, is wellknown to have important roles in tissue browning and melanin formation, as well as in the induction of spore dormancy in A. bisporus (Oka et al, 1981;Rast et al, 1979; Stussi and Rast, 1981;Vogel and Weaver, 1972).…”
Section: Resultsmentioning
confidence: 99%
“…Mushroom tyrosinase (EC 1.14.18.1; monophenol, dihydroxyphenylalanine:oxygen oxidoreductase), l-DOPA, pyrocatechol, and various phenolic acids except the three phenolic acids specified below were obtained from Sigma Chemical Co. (St. Louis, MO). 7-L-Glutaminyl-4-hydroxybenzene (GHB) was extracted from the gill tissue of mushroom following the procedure of Rast et al (1979) and identified by UV and NMR spectroscopy (1H NMR spectra were obtained with a JEOL GX-400 instrument with D20). Vanillic, gentisic, and sinapic acids as well as sodium periodate were purchased from Aldrich Chemical Co. (Milwaukee, WI).…”
Section: Introductionmentioning
confidence: 99%